DDIS-01. NEW DRUG DISCOVERY WITH DRUG RE-POSITIONING SYSTEM TOWARD GBM TREATMENT. (11th November 2019) - Michiue, Hiroyuki; Tsuboi, Nobushige; Hayashi, Keiichiro; Matsui, Hideki; Kurozumi, Kazuhiko
Abstract: INTRODUCTION: Invasion of Glioblastoma (GBM) cells into normal brain is the major cause of poor prognosis and requires dynamic reorganization of the actin cytoskeleton, which includes lamellipodial protrusions, focal adhesions, and stress fibers at the leading edge of GBM cells. Therefore, we hypothesized that the inhibition of actin polymerization with existing medication could lead to clinical GBM treatment directly in short time. The Drug Repositioning system is also known as drug repurposing or drug reprofiling and understood as the process of redeveloping a compound for use in a different disease. In this time, we would show the new direction of drug development with drug repositioning. MATERIALS AND METHODS: We adopted a drug repositioning system for screening with a pyrene-actin-based actin polymerization assay and identified fluvoxamine, a clinically used antidepressant. Fluvoxamine, selective serotonin reuptake inhibitor, was a potent inhibitor of actin polymerization and confirmed as drug penetration through the blood–brain barrier (BBB) and accumulation of whole brain including brain tumor with no drug toxicity. RESULTS: Fluvoxamine inhibited serum-induced ruffle formation, cell migration, and invasion of human GBM and glioma stem cells in vitro by suppressing FAK signaling. Fluvoxamine showed no drug toxicity. Daily treatment of athymic mice bearing human glioma-initiating cells with fluvoxamine blocked tumor cell invasion and prolonged the survival with almost same doze of anti-depressant effect. CONCLUSIONS: The SSRI group has big potential for clinical GBM treatment with low cost, short time and low side effect.